2016
DOI: 10.4103/1658-354x.174918
|View full text |Cite
|
Sign up to set email alerts
|

Basic concepts for sample size calculation: Critical step for any clinical trials!

Abstract: Quality of clinical trials has improved steadily over last two decades, but certain areas in trial methodology still require special attention like in sample size calculation. The sample size is one of the basic steps in planning any clinical trial and any negligence in its calculation may lead to rejection of true findings and false results may get approval. Although statisticians play a major role in sample size estimation basic knowledge regarding sample size calculation is very sparse among most of the ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(104 citation statements)
references
References 8 publications
0
101
0
3
Order By: Relevance
“…The percentages of each sample size calculation parameter being reported in 2016 was higher than in a Bold values used to distinguish them as the culmination of the items Data presented are the number of trials with the specific criterion reported/number of eligible trials (%) unless otherwise specified. Percentages may not sum to 100% because of rounding 1 Number of trials where the actual value was within 10% of the assumed value/number of trials with both the specific assumption and the actual value reported (%) 2 For trials using a continuous outcome in their sample size calculation 3 Number of trials where the replicated initial sample size was within 10% of the reported target sample size/number of trials with all sample size assumptions reported (%) 4 Subgroups were not mutually exclusive so percentages sum to over 100%…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentages of each sample size calculation parameter being reported in 2016 was higher than in a Bold values used to distinguish them as the culmination of the items Data presented are the number of trials with the specific criterion reported/number of eligible trials (%) unless otherwise specified. Percentages may not sum to 100% because of rounding 1 Number of trials where the actual value was within 10% of the assumed value/number of trials with both the specific assumption and the actual value reported (%) 2 For trials using a continuous outcome in their sample size calculation 3 Number of trials where the replicated initial sample size was within 10% of the reported target sample size/number of trials with all sample size assumptions reported (%) 4 Subgroups were not mutually exclusive so percentages sum to over 100%…”
Section: Discussionmentioning
confidence: 99%
“…3 An inadequately small sample size may result in the inability to detect a precise effect, if present, while a needlessly large sample size may result in extra participants being exposed to the potential risks of the trial. 4 While there are ethical debates over whether underpowered trials should be conducted, most researchers agree that an a priori sample size calculation should still be conducted and reported to ensure methodologic quality. 5 The Consolidated Standards of Reporting Trials (CONSORT) statement is a set of guidelines aimed at improving the quality of RCT reporting.…”
Section: Résumémentioning
confidence: 99%
“…Li et al reported variances in iodine content and normalized slope of 0.4 mg/mL and 0.45 between benign and malignant lesions, respectively, in ex vivo evaluations [14]. In this study, a difference in iodine content of at least 0.4 mg/mL was considered a desirable result [21]. For a two-sided 5% significance level and 80% power, we estimated that a sample International Journal of Endocrinology size of at least 10 nodules in each group was needed to detect this difference.…”
Section: Statistical Analysesmentioning
confidence: 76%
“…Tampoco es razonable (particularmente en estudios dónde se hará alguna intervención) someter a los participantes a riesgos, cuando con un número menor es posible lograr los objetivos de la investigación. 2,3 En general, para quienes están elaborando su protocolo de investigación, especialmente cuando se tiene poca experiencia, el cálculo del tamaño puede resultar una tarea complicada. El objetivo de este artículo es dar a conocer los aspectos más importantes para calcular de manera juiciosa, el número necesario de participantes en un estudio de investigación clínica, tomando como base a otros autores que han escrito extensamente sobre el tema.…”
Section: 2unclassified